Association between modes of delivery and postpartum dietary patterns: A cross-sectional study in Northwest China - Zhao, Lingxi; Wang, Lianlian; Wang, Wenling; Shi, Zumin; Zhu, Yuzhao; Li, Shengping; Wang, Tiankun; Su, Yu; Li, Zhourong; Wen, Yaqi; Zhang, Laixi; Xu, Qi; et al. (Frontiers in Nutrition, 2022)
Objective: Puerperae’ dietary patterns(DPs) during the puerperium may be influenced by the mode of delivery, but population studies on this topic are scarce. This study aims to explore the relationship between DPs and different modes of delivery among puerperae. Methods: A cross-sectional study was conducted on 3345 parturients in Lanzhou, China. The postpartum food intake was measured by a food-frequency questionnaire (FFQ). Factor analysis was used to determine the DPs. Multiple linear regression was employed to examine the association between the mode of delivery and DP. Results: In this study, two DPs, i.e., traditional and modern DPs, were identified. Traditional DP was characterized by high energy-adjusted intake of tubers, coarse cereals, rice, whole grains, fishery products and eggs. Modern DP included a high intake of coffee, nonsugary drinks, wine, tea and fishery products. Compared with participants with vaginal delivery (reference category), caesarean section had an inverse association with modern DP (β: −0.08; 95% CI: −0.29, −0.03). A significant interaction was found between age, education level and modes of delivery. The inverse association between caesarean section and modern DP or the intake of coffee was significant among second-birth puerperae under 35 years of age. Moreover, among the participants with high education, caesarean section was positively associated with intake of vegetables. Conclusions: Caesarean puerperae with higher levels of education and those under the age of 35 years had less unhealthy foods intake than those who had vaginal delivery. They need to be accounted for in educational programs and interventions focused on healthy diet recommendations in puerperium.